Efficacy of HPA Lanolin® in treatment of lip alterations related to chemotherapy - Paulo Sérgio da Silva Santos; José Endrigo Tinôco-Araújo; Lucas Monteiro de Vasconcelos Alves de Souza; Rafael Ferreira; Maura Rosane Valério Ikoma; Ana Paula Ribeiro Razera; Márcia Mirolde Magno de Carvalho Santos (University of São Paulo, 2013)
The side effects of chemotherapy on the lips may cause esthetic and functional impact and increase the risk of infection. HPA Lanolin® is an option for supportive therapy because it has anti-inflammatory, antimicrobial and moisturizing properties. Objective: To evaluate the efficacy of this product in the prevention of lip alterations in a population of patients undergoing chemotherapy. Material and Methods: Patients undergoing chemotherapy (n = 57) were examined and distributed into two groups: study (used HPA Lanolin®) and control (without supportive therapy on the lips). We evaluated the patients two weeks after chemotherapy, registering oral alterations, symptoms of pain, discomfort, limitation of mouth opening and dehydration, classified according to a visual analogue scale. Results: Patients who used HPA Lanolin® had lower dehydration and experienced improvement of lip dryness (p<0.001). The main symptoms were dehydration, discomfort, limitation of mouth opening, pain. The main clinical signs were dry lips, mucositis, cheilitis, hematoma, swelling and cracking. We found no difference concerning the variables of pain, discomfort, and limitation of mouth opening between the study and control group. Conclusions: We suggest that HPA Lanolin® is effective in reducing the symptoms of dehydration and the signs of lip dryness resulting from toxicity of chemotherapy, proving to be an interesting alternative supportive therapy for cancer patients.